Kinerja Penyuluh Agama Islam Fungsional dalam Pembinaan Umat di Kota Padang - Wahab, Zainul (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2019)
Islamic Religious Instructor is very important and strategic, in addition to carrying out guidance and counseling, it also provides information and motivation on the implementation of development programs to the community. This shows that the Islamic Religious Instructor as a guide of the people in the field of religion also plays a role as a community figure. This role is the main task for a religious instructor in the context of upholding the amar ma'ruf nahi munkar which aims to increase the community's faith and piety to Allah SWT so that people become religious, virtuous and have a social attitude to others. As community leaders or leaders, religious instructors will become the foundation for the community in solving various problems of life, even they are expected to be able to provide changes, as well as motivators, dynamists and mobilizers in physical and mental development. Islamic Religious Instructor as the spearhead of the implementation of guidance or counseling to the community in the religious field, has a strategic role in realizing education in society through religious language.